A crusade over the airwaves: the Blue Division on Radio Nacional de España (1941–1954) - Gómez García, Salvador; Martín Quevedo, Juan (Historical Journal of Film, Radio and Television, 2017)
The Blue Division, Spain’s most notable military contribution to the Second World War, has been examined from many different perspectives, though the role of communication has not featured among them. This study aims to analyse the role played by Spanish state radio in the creation and maintenance of Spain’s war effort in that period. In order to achieve this, we used documentary sources, and more specifically, reconstructed the radio programming schedules, mainly using the press, due to the lack of audio recordings from the era. Finally, this work explores the role of radio from the Blue Division’s inception through to its official disbandment; or, put another way, the transition from commitment to the Axis powers to gradual estrangement from them. A dual transition process occurred on Radio Nacional de España: firstly, from zealous glorification to the silencing of the divisionaries by official order. The second transition was from a radio station that, since the Civil War, had lost its persuasive power, to a new perception of propaganda based on the familiar and the emotional.
Keywords: Scopus; WOS